Fair Use Doctrine in Photocopying Books for Educational Purposes: A Study of Copyright Acts in Indonesia and the United States - Nadiya Nurmaya; Mardi Handono; Galuh Puspaningrum (Indonesian Journal of Law and Society, 2020)
Globalization has offered a multitude of opportunities and challenges, mainly when it deals with copyright. The scope of copyright has been broad, encompassing various aspects of life, especially in literature and education. This study aims to analyze Indonesia's copyright issues, particularly regarding the reproduction of books deemed to have lesser protection for authors, dealing with the fair use doctrine. This doctrine considers that work is allowed to a limited extent for use by other parties without the creator or copyright holder's permission to keep it fair. This fair use doctrine permits limited and fair use of literary works for specific purposes without royalty payments and the author's consent. Given the author's more protection, this study then displays a comparative analysis of the U.S. framework on the Copyright Act portrayed into two main discussions. First, this study will discuss photocopying for educational purposes from the lens of Indonesia's Copyright Act. Second, this study considers the possible adjustment to adopt the so-called future concept of restrictions for educational purposes from the U.S. States Copyright Act 1976. KEYWORDS: Fair Use Doctrine, Copyright Act, Copyright for Educational Purposes.